Labu sayong / Nurul Ayn Ahmad Sayuti ... [et al.] - Sayuti, Nurul Ayn Ahmad; Mohd Amin, Mohd Hamidi Adha; Ab Hamid, Abu Hanifah (Universiti Teknologi MARA, Kedah, 2018)
Hybridity can be defined as the fusion of cultural elements or the incorporation of foreign elements in culture. The idea of incorporating the cultural aspects into daily products design is another way of preserving the cultural product identity. This project is looking into the potential of Labu Sayong in product design perspective by incorporating the artistic elements and the philosophy of Labu Sayong into a contemporary daily use product design. Labu sayong is a gourd pitcher that is made of clay. It is a handicraft of the Perak Malays from a small village named Sayong near Kuala Kangsar. Labu Sayong is known as a water container and is used to cool down the water temperature. It is one of the national heritage that needs to be preserved. Researches have shown that there is an urgent need to sustain the legacy of Labu Sayong making and designs. However, in term of design, Labu Sayong has never really changed. Although it is vital to sustain this handmade craft industry, with the emergence of technology in pottery making techniques, the traditional handmade Labu Sayong has faced challenges. In order to be integrated into the new innovative and contemporary design, Labu Sayong will go through several transformations or developments for the chances to be fully recognised in the global world.